Democracia participativa no contexto latino-americano: entre o Estado, os heróis e a sociedade civil - Ribeiro, Agatha Justen Gonçalves (2016)
This thesis proposes to examine if institutional changes to introduce and expand direct/participatory democracy in public administration can promote real changes on SocietyState relationship in capitalist Nations. To this end, we analyse the constitutional models adopted in recent years in Latin American countries. We consider the historical process that justifies the emergence of the discussion about social participation mechanisms that are alternative to vote and how that discussion have been gone into the political agenda of some Latin American countries until being institutionalized. Theoretically, we examine the processes of institutionalized participation in the references countries – Bolivia, Ecuador and Venezuela. We consider the Brazilian case, because it is pioneer and because it is one of the most important countries in this region. We study carefully Bolivia, which recently appears as the most successful case. Methodologically, our epistemological base is dialectics. In addition, we do discursive analyses. Our hypothesis is that those changes, although represent political progress, have historical and structural limitations which prevent to achieve a high level of citizenship and the sustainability of those advances.